Sustainability in engineering programs in a Portuguese Public University - Ciliana Regina Colombo; Anabela Carvalho Alves (Production)
Abstract Rethink the interventions, human practices and their effects on the natural environment, for the preservation of life and biodiversity, threatened by the capitalist model of production, consumption and disposal, becomes each day more indispensable. The role of universities as knowledge building space is fundamental for the insertion of the environmental approach (greening) in its various fronts (education, research, extension, and management). Following the line of several types of researches about the subject, this paper aims to identify if and how the issue of sustainability (e.g. through Project-Based Learning use) is taught in the various engineering programs of a Portuguese Public University. This study was carried out by a documental research based on the programs´ curricula published in the official website of the university. The engineering programs selected included integrated master, master (second cycle) and doctorate (third cycle). In this study, it was identified programs that are more focused on sustainability concepts than others, so the programs were classified in three categories: strongest, medium and weakest focus.